loyiha TEXNOLOGIYASI yarimo‘tkazgichlar fizikasini o‘qitish sifatini yaxshilash USULI sifatida - Ametov, R.A. (SCIENCE and SOCIETY, 2021)
The article considers the project method as a motivating tool for students in the study of semiconductor physics, allowing them to increase their interest in the subject, which in turn helps to improve the quality of education.